Penaksiran Generalized Method of Moments dengan Penggunaan Metode Marquardt-Levenberg - Nurul Mukhlisah Abdal; Wahyudin Nur; Ainun Mawaddah Abdal (Indonesian Journal of Fundamental Sciences, 2020)
Generalized Method of Moments is a method for estimating parameters using sample moments. GMM is used by the researcher particularly in economics to determine econometrical models which their distribution function is hardly known. Not only for economics, but GMM also is useful for agriculture, transportation, health care, etc. Research methodology for this article is review of literature. This article describes the combination of GMM and Marquardt-Levenberg algorithm along with the example of its use